Synthesis of allyl-aziridines from α-halo oxime ethers and allyl zinc bromides. Issue 31 (15th March 2016) - Zheng, Songlin; Zhang, Songlin
Abstract : A novel method for the preparation of allyl aziridines by reacting α-halo oxime ethers with allylic zinc reagents under mild conditions. Some advantages of using organozinc reagents are that they are easily prepared, non-toxic, and more selective than Grignard reagents. Abstract : A novel method for the preparation of substituted allyl aziridines by reaction of α-halo with allylic zinc reagents in mild conditions is reported in this paper. The present method complements the existing synthetic methods due to some advantages offered by the use of organozinc reagents, which are easily prepared, relatively stable and non-toxic, and more selective than Grignard reagents.